Philosophical and Legal Interpretations of the Deformations of Legal Awareness in the XX - Early XXI Century - M. V. Melnyk (Bulletin of Kharkiv National University of Internal Affairs)
It has been stressed that the topic of philosophical and legal interpretations of the deformations of legal awareness in the XX – early XXI century is actively developed by scholars of the countries of the post-Soviet space. Emphasis has been placed on the development of the doctrine on legal nihilism that has been developed in Western European philosophical and legal thought, as well as on the problem of totalitarian legal awareness that has emerged in Soviet society.